ANALYSIS OF MICHEL FOUCAULT MODEL POSTFEMINISM IN NAJWA EYE HOLIDAYS WITH THE THEME WOMEN'S POLITICS (WHO IS CAPRES CARING FOR WOMEN) - Lili Liana; Bella Novita; Rochmat Tri Sudrajat (IKIP Siliwangi, 2020)
Television is a reliable container or strategy for social and political groups so that it appears based on the discourse process. One of the programs shown is the Mata Najwa talk show with women's political themes and coming from speakers who are struggling in politics. This event various kinds of discourse formation practices can emerge. A good discourse should give a clear and intact shadow to the opponent so that it does not cause many perceptions. Not only good and clear, but the intended discourse or question can trigger the speaker to actually speak so that the truth can be known. In this analysis, Michel Foucault's post-feminism discourse analysis uses language as the article freedom of feminist discourse in the Mata Najwa program. The article analyzes women's discourse relating to the freedom of women as seen from a variety of oppressions within feminists. This study uses a qualitative descriptive design, with an observation method as a method of data collection. The results of this study are seven discourses related to post-feminism and the power offered by the presidential candidate to feminists.Postfeminism Analysis, Mata Najwa